CHARACTER VALUE IN KARAWITAN ACTIVITY: A QUALITATIVE STUDY AT SDN TRUCUK BANTUL INDONESIA - Altisa Dini Prastiwi; An-Nisa Apriani; Riki Perdana (Universitas Indraprasta PGRI, 2021)
This study aims to describe the integrated character values in Karawitan activities and the impact of these activities on the personalities of students. A research method is a qualitative approach with a descriptive research type. Data collection using observation and interviews technique. The observed character values are Religious Values, Nationalism, Independence, Teamwork, and Integrity. Participants in this study were students in grades 3,4,5 at SDN Trucuk Pajangan Bantul. The sampling technique used was snowball sampling. The results showed that all the character values studied were integrated with Karawitan activities. Religious value is shown from the behavior of implementing religion, tolerance, and peace. The value of nationalism is shown in the attitude of selfishness, love for the country, and obeying the rules. The independent value of students is shown by the behavior of working hard, professionally, and not depending on others. The value of mutual cooperation is shown in the behavior of completing work together, solidarity, and helping each other. The value of integrity is shown from responsible, active behavior and in accordance with words and actions. Recommendations for further research are to integrate karawitan activities into several learning topics so that they have a direct influence on student achievement.